Impact of China on Indian Garment Industry - Marwaha, Aditya (2008)
To survive and succeed in garment manufacturing business in today era of globalisation and increasing competition, it is important for firms to analyse the environment in which it is working. With cutting margins between the cost and the selling price, firms have to make efforts to decrease their cost. Therefore, various factors, in the form of theories, affecting the success of a firm and the cost of a product are critically evaluated during the literature review. The theories are global competition; strategic management; PEST analysis; five competitor force model; and resource based view. The interviews of garment manufactures were gained so as to get an insider view of this industry and gain the practical side with their relation to the theories. Integration of China in the global economy is one of the most significant developments that is affecting the structure and evolution of the global system. This research mentions what factors is China ahead of India in the garment industry. A comparison will be made with the garment industry in China, as they are the biggest competitor. This industry in India needs to be improved, and for this, various recommendations are outlined which would help enhance the competitive position of the Indian garment industry in the period of global competition.